2012
DOI: 10.1088/1748-9326/7/3/035402
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the depositional environment upstream of Potanin Glacier, Mongolian Altai, from pollen analysis

Abstract: This study analyzed pollen in snow pits dug in September 2008 and September 2009 upstream of Potanin Glacier in the Mongolian Altai Mountains, which is a summer accumulation-type glacier, to investigate the environment for recent snow deposits. The snow pit observations in both years were carried out at sites 0 and 4, which are 3752 and 3890 m above sea level, respectively. Seasonal layers of the pits were identified according to the taxon of pollen scattered during different seasons. In the 2007 and 2008 laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 7 publications
2
18
0
1
Order By: Relevance
“…For example, on the Alto dell'Ortles, fresh winter snow usually accumulates in windy conditions and has a density of 300 kg m −3 (Gabrielli et al, 2010). Similar values are reported by Nakazawa et al (2012Nakazawa et al ( , 2015. In contrast, snow deposited at other sites with low wind conditions could show lower density (50-70 kg m −3 ) and higher porosity, which would facilitate the vertical transport of pollen grains.…”
Section: Meltwater Effect On the Pollen Signalsupporting
confidence: 55%
See 1 more Smart Citation
“…For example, on the Alto dell'Ortles, fresh winter snow usually accumulates in windy conditions and has a density of 300 kg m −3 (Gabrielli et al, 2010). Similar values are reported by Nakazawa et al (2012Nakazawa et al ( , 2015. In contrast, snow deposited at other sites with low wind conditions could show lower density (50-70 kg m −3 ) and higher porosity, which would facilitate the vertical transport of pollen grains.…”
Section: Meltwater Effect On the Pollen Signalsupporting
confidence: 55%
“…In order to overcome this latter issue Nakazawa et al (2011Nakazawa et al ( , 2005Nakazawa et al ( , 2004) adopted a simplified approach, focusing on three main taxa (Pinaceae, Betulaceae and Artemisia) that are representative of the three corresponding flowering seasons (spring, early summer, late summer). By doing so, they were able to detect seasonal changes in ice cores from the Altai (Nakazawa et al, 2015(Nakazawa et al, , 2012(Nakazawa et al, , 2006(Nakazawa et al, , 2005. Finally, there is little knowledge about the effects of percolating water on the palynological signal; only two studies directly addressed this issue, and they obtained contrasting results (Ewing et al, 2014;Nakazawa and Suzuki, 2008).…”
Section: Festi Et Al: Linking Pollen Deposition and Snow Accumulamentioning
confidence: 99%
“…The pollen record (as an independent biological proxy) from a Bolivian ice cap (Sajama) shows the same paleoclimatic trend as registered by the traditional chemical and physical parameters in two Peruvian ice cores hundreds of kilometers away and suggests that climatic changes associated with the LIA occurred synchronously across the central Andes . Studies of snow pits and an ice core in the Russian Altai demonstrated the potential for identifying and separating seasonal layers with high resolution by analyzing pollen taxa in samples as small as 10 mL (Nakazawa et al, 2004(Nakazawa et al, , 2005(Nakazawa et al, , 2012. Ice core pollen data from the Belukha glacier suggest distinct forest diebacks and the expansion of steppe in response to dry climatic conditions (Eicher et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Because this was the first time this glacier was observed, the main purpose of the present study is to investigate the recent snow depositional environment at the upstream part of the glacier using an ice core and particularly to understand the melting status of this glacier. Recent snow pit and ice core studies in the Russian and Mongolian Altai Mountains demonstrated the potential for high-resolution identification and separation of seasonal layers through analysis of pollen taxa in samples as small as 10 mL (Nakazawa et al, , 2005(Nakazawa et al, , 2011(Nakazawa et al, , 2012. Pollen grain production and dispersal follow a distinct seasonal phenology depending on the taxon.…”
Section: Introductionmentioning
confidence: 99%
“…Pollen grain production and dispersal follow a distinct seasonal phenology depending on the taxon. In addition, pollen grains under snow cover have also been shown not to move toward lower layers upon significant melting, but rather remain at the melting surface Suzuki, 2008 andNakazawa et al, 2012). Therefore, we focused on the advantages of the pollen analysis approach and analyzed the ice core collected from Gangjoe La Glacier.…”
Section: Introductionmentioning
confidence: 99%